Alcohol use, risky sexual behavior, and condom possession among bar patrons. (September 2016) - Chaney, Beth H.; Vail-Smith, Karen; Martin, Ryan J.; Cremeens-Matthews, Jennifer
Abstract: Purpose: The current study seeks to: 1) assess the relationship between alcohol consumption and intentions to engage in unprotected sex in an uncontrolled environment, and 2) to identify if covariates (race, age, sex, breath alcohol content (BrAC), intentions to engage in sex, hazardous drinking rates) are significant predictors of condom possession during time of uncontrolled alcohol consumption. Methods: Data were collected from 917 bar patrons to assess alcohol use using the Alcohol Use Disorders Identification Test (AUDIT-C), BrAC levels, intentions to engage in risky sex, and condom possession. Correlational analysis and hierarchical binary logistic regression was conducted using SPSS. Results: Correlational analyses indicated a negative relationship between AUDIT-C scores ( r  = − 0.115, p  = 0.001), BrAC ( r  = − 0.08, p  = 0.015), and intentions to use a condom. Over 70% of participants intended to use a condom if they engaged in sex; however, only 28.4% had a condom to use. The regression analysis indicated the predictive model (χ 2  = 114.5, df = 8, p  < 0.001) was statistically significant, and correctly classified 72.9% of those in possession of a condom. Conclusions: Alcohol consumption was associated with intentions to have unprotected sex; however, intentions to engage in protected sex and condom possession were higher for males and those with higher BrAC levels. Highlights: Bar patrons' intentions to engage in unsafe sex varied by sex and BrAC. Significant predictors of condom possession were gender, race, age and BrAC level.